Inhibitory mechanisms of amentoflavone on amyloid-β peptide aggregation revealed by replica exchange molecular dynamics - Suxia Wu; Chang Liu; Yang Li; Xiaoyu Zhang; Qianji Han; Heng Zhao; Kun Zhao; Yaru Dang; Ruihan Wang; Shitao Song (Scientific Reports)
Abstract Amyloid-β (Aβ) aggregation is a central pathological hallmark of Alzheimer’s disease, with soluble trimers recognized as particularly neurotoxic species. Amentoflavone (AMF), a natural biflavonoid compound, has shown strong inhibitory effects on Aβ aggregation. However, its underlying molecular mechanism remains poorly understood. In this study, we employed replica exchange molecular dynamics (REMD) and molecular mechanics/Poisson–Boltzmann surface area (MM/PBSA) method to elucidate the interaction between AMF and Aβ peptides. Our results reveal that AMF preferentially binds to the 16KLVFFAEDV24 segment, a hydrophobic core that plays a critical role in the initiation of aggregation. It disrupts b-sheet formation through hydrophobic interactions with Leu-17, Phe-20, and Val-24. This binding stabilizes disordered coil conformations and prevents the conformational transitions required for fibril formation. Based on these findings, we performed structure-based virtual screening and identified two natural product-derived candidates with higher predicted affinity. These insights provide an atomic-level understanding of AMF’s inhibitory mechanism and support the rational design of natural product-inspired inhibitors that target Aβ aggregation.